주관적 빈곤 청소년의 정신건강 영향요인 - 김미진(Mi Jin Kim); 정정희(Jeong Hee Jeong) (보건교육건강증진학회지, 2019)
Objectives: The purpose of this study was to identify the factors that influence the mental health in Korean youth in subjective poverty. Methods: Data were collected from the 13th 2017 Korea Youth Risk Behavior Web-Based Survey. There were 8,892 people in total who participated in the same survey. The data were analyzed using descriptive statistics, χ2-test, and multiple logistic regression analysis. Results: The mental health of youth in subjective poverty was characterized by a stress level of 87.1%, depression rate of 34.3%, and suicidal tendency at 19.9%. The mental health of youth in subjective poverty was worse than the youth who were not. The socio-demographic factors found to influence mental health were gender, grade, and counseling. Among health risk behaviors, the relevant factors found were drinking, smoking, unprotected sex, and drug use. The most significant factors affecting mental health were found to be gender and drug use. Conclusions: Based on the findings of this study, it is important that mental health intervention programs should consider improvement of not only socio-demographic factors, but also health risk behaviors to improve mental health in Korean youth in subjective poverty. KCI Citation Count: 0